Sistem Informasi Persediaan Barang Konsinyasi Dengan Metode Perpetual Moving Average - Andhika Novandya; Agung Maulana (IMTechno: Journal of Industrial Management and Technology, 2020)
Computers are devices that are created to facilitate human work, while making progress in both hardware and software manufacturing. A company today is in need of information that supports and provides satisfactory service to its customers. For this reason, research is needed on the merchandise inventory information system with a consignment system whose data processing has not been computerized. The case study in this research is a company engaged in the sale of toys with a cosignment inventory system using the perpetual average moving method. The existing system in toy supply companies is still done manually, starting from ordering goods, storing data relating to the inventory process, to making reports. Manual recording allows errors in recording during the process, inaccurate reports and delays in finding the required data. Computer-based information system design is the best solution to solve the problems that exist in this company. With a computerized system, an effective and efficient activity can be achieved in supporting the activities of this company. Therefore, with a better computerized system, in order to run more effectively and efficiently and the current inventory system is more conducive than the previous system.